IFN-I inducible miR-3614-5p targets ADAR1 isoforms and fine tunes innate immune activation - Vuillier, Françoise; Li, Zhi; Black, Iain; Cruciani, Melania; Rubino, Erminia; Michel, Frédérique; Pellegrini, Sandra (Frontiers in Immunology, 2022)
Regulation of innate immune responses is essential for maintenance of immune homeostasis and development of an appropriate immunity against microbial infection. We show here that miR-3614-5p, product of the TRIM25 host gene, is induced by type I interferon (IFN-I) in several human non-immune and immune cell types, in particular in primary myeloid cells. Studies in HeLa cells showed that miR-3614-5p represses both p110 and p150 ADAR1 and reduces constitutive and IFN-induced A-to-I RNA editing. In line with this, activation of innate sensors and expression of IFN-beta and the pro-inflammatory IL-6 are promoted. MiR-3614-5p directly targets ADAR1 transcripts by binding to one specific site in the 3'UTR. Moreover, we could show that endogenous miR-3614-5p is associated with Ago2 and targets ADAR1 in IFN-stimulated cells. Overall, we propose that, by reducing ADAR1, IFN-I-induced miR-3614-5p contributes to lowering the activation threshold of innate sensors. Our findings provide new insights into the role of miR-3614-5p, placing it as a potential fine tuner of dsRNA metabolism, cell homeostasis and innate immunity.